THE VALUE OF THE KINETIC REACTION ORDER DETERMINED BASED UPON THE CONDITIONAL OPTIMALITY DOCTRINE FOR THE MULTI-OPTIONAL FUNCTIONS ENTROPY - Гончаренко, Андрій Вікторович (Problems of Friction and Wear, 2019)
It is made an attempt to propose some appropriate models of the friction and wear processes that could happen in the considered structural elements of the engineering units. The uncertainty measure in the given consideration is the entropy of the special hybrid-optional effectiveness functions. Such kind of entropy originates from the Jaynes’ principle, being adapted to the subjective entropy maximum principle, with the implementation possibilities to the applicable fields of aviation industry as that follows the readings of the references. The paper theoretically considers the possibility of the multi-optional hybrid functions entropy conditional optimization doctrine applicability with the purpose of discovering a substantiated reason for the special hybrid-optional effectiveness functions existence, as well as the reasons for the formula optimality. The order of the kinetic reaction as a model function, or the so-called dependence of the tribological process order as a function, formula is obtained with taking into account the degree of uncertainty for a certain type hybrid-optional effectiveness functions. With the help of the variational principle it is shown the optimality of the formula. The evolution of the proposed at this paper approach from the subjective analysis to the hybrid multi-optional functions optimization doctrine implies the use of the hybrid multi-optional functions, as an objectively existing characteristic of a phenomenon, instead of the subjectively preferred, by a human, functions, since no one chooses the objectively existential reality. The approach has a significance of a plausible explanation for the phenomena stipulated by multi-optionality.